Personal Hygiene and Sanitation in Cafeterias at University X in Depok, Indonesia - Fitria, Lassie; Susanna, Dewi; Eryando, Tris (KnE Life Sciences, 2018)
The study aimed to identify personal hygiene and sanitation practices among 99 food handlers working in the cafeterias at University X. This was a cross-sectional study. The research was conducted between April and July 2016 in a university in Depok, Indonesia. There are 16 cafeterias at the university. Purposive sampling methods applied. The population of this research was the food handlers in the university’s cafeterias. The laboratory test that detected the number of worm eggs/gram in participants’ feces was applied to determine the worm infection. Information on the participants’ personal hygiene and the sanitation of the cafeteria facilities was collected through interviews and observation. The results showed that four participants had intestinal parasitic worm infections.A personal hygiene assessment found that 83% of participants did not have appropriate hygiene, and95% of the cafeterias had inadequate sanitation of faclities. Certification, medical checkups for food handlers, and regular training insafe food handling practices should be considered. Keywords: Worm, intestinal parasite, feces, personal hygiene, sanitation